2007 IEEE International Conference on Portable Information Devices 2007
DOI: 10.1109/portable.2007.61
|View full text |Cite
|
Sign up to set email alerts
|

Integrable High-Efficiency AC-DC Converter for Piezoelectric Energy Scavenging System

Abstract: In recent years a lot of studies focused on Energy-Scavenging Systems (ESS). An important motivation for these studies is the development of Portable Devices (PD) and of Wireless SensorsNetwork (WSN). An ESS can be partitioned in two sections: the energy-scavenger itself and the electronic interface. The first one is the energy transducer while the second one is the electronic circuit which manages the energy. One of the most important objectives of the electronic interface is to realize the required ac-dc con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Full-bridge rectifiers [7], [8] and voltage doublers [5], [9] are commonly used as rectifier circuits to convert the AC output of a piezoelectric harvester into a DC voltage. Typical implementation of these rectifier circuits is shown in Fig.…”
Section: A Full-bridge Rectifiers and Voltage Doublersmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-bridge rectifiers [7], [8] and voltage doublers [5], [9] are commonly used as rectifier circuits to convert the AC output of a piezoelectric harvester into a DC voltage. Typical implementation of these rectifier circuits is shown in Fig.…”
Section: A Full-bridge Rectifiers and Voltage Doublersmentioning
confidence: 99%
“…This reduces the magnitude of the flipped voltage and hence reduces the overall power output. The amount of power reduction can be found by including this additional resistance to the value of in (9). The other issue with inductor sharing is that there may be a delay of up to 4 s from the time the bias-flip rectifier requests the inductor till when it is granted access.…”
Section: A Effect Of Inductor Sharing On System Performancementioning
confidence: 99%
“…Figure 2a shows the active topology of the ac-dc converter that uses comparators CMP1 and CMP2 to drive switches S1 and S2. The comparators sense the drain to source voltages of the two MOSFETs and properly turn them on or off [11]. This is the most straightforward way to implement an active version of the voltage doubler converter, since the switches and their driving emulate some ideal diode with a very low, almost zero, forward voltage drop, but the design of the two comparators is critical because a very accurate choice of the threshold voltages is required.…”
Section: Design Of the Proposed Front-end Circuitries: Common Partsmentioning
confidence: 99%
“…1). Of course the active circuitry comes at the price of using a part of the harvested energy to supply the active circuitry itself: active converters can be more efficient than passive solution [3][4], [11], but they are more difficult to be designed because their whole power consumption has to be very low.…”
Section: Introductionmentioning
confidence: 99%
“…Standard full-bridge rectifiers (Jeon et al, 2005;Ottman et al, 2002) and voltage doublers (Dallago et al, 2007;Le et al, 2006) are the most common rectifier circuits reported in energy harvesting review but the main source of power losses are typically the diodes forward drops. Alternatively, voltage multiplier rectification is possible because of its capability to produce higher DC voltage.…”
Section: Introductionmentioning
confidence: 99%